Research on the Interaction Method that Can Alleviate Cybersickness in Virtual Reality Games - Lu, Zhenyu; Mao, Ruozhou (HCI in Games: Serious and Immersive Games, 2021)
Cybersickness is a symptom that is common among game players. Although each player has a different level of symptom, this feeling will occur during the long-term experience of video games. Studies have shown that cybersickness is caused by many factors, including display hardware, screen content, and human factors. With the development of VR game platforms over the years, cybersickness has become a high-priority in the virtual reality industry, and cybersickness has also been called VR sickness. There have been many different studies on how to alleviate VR sickness, such as adding a virtual nose model to the content, providing Dynamic Gaussian Blur, using Dynamic FOV, etc. These studies are focused on reducing VR sickness by improving the displayed content. Not like previous studies, in this paper, we looked forward to discussing the VR sickness that was caused by different interaction. In this study, the researchers designed several VR interactions based on different hardware. Then they organized user tests that asked testers to complete several goals in the same VR environment. After comparing multiple sets of test data, the researchers discussed the possibility of an interaction method that will reduce VR sickness and how it looked like. Through this work, we tried to give an insight into the current research findings of alleviating VR sickness and discussing the possibility of long-term VR interaction. In this context, this study aimed to explore a virtual reality interaction method that allows players to alleviate VR sickness during gaming.